Narrowband-IoT (NB-IoT) and IoT Use Cases in Universities, Campuses, and Educational Institutions: A Research Analysis - Taruc, Lyberius Ennio F.; De La Cruz, Arvin R. (International Journal of Computing Sciences Research, 2024)
Purpose – The main objective of this research paper is to analyze the available use cases of Narrowband-IoT and IoT in universities, campuses, and educational institutions. Method of Research – A literature review was conducted using multiple databases such as IEEE Xplore, ACM Digital Library, and Scopus. Results – The study explores the benefits of IoT adoption in higher education. Various use cases of NB-IoT in educational institutions were analyzed, including smart campus management, asset tracking, monitoring, and safety and security systems. Of the six use cases assessed, three focused on the deployment of IoT Things, while three focused on NB-IoT Connectivity. Conclusion – The research paper concludes that NB-IoT technology has significant potential to enhance various aspects of educational institutions, from smart campus management to improving safety and security systems. Recommendations – The study recommends further exploration and implementation of NB-IoT technology in educational settings to improve efficiency, security, and overall campus management. Research Implications – The research highlights the potential applications of NB-IoT in universities and educational institutions, paving the way for future studies in this area. Social Implications – The social implications of this research could involve enhancing the overall learning experience for students, improving campus safety, and promoting technological advancements in educational settings.